Coated ternary material doped with different particle sizes, preparation method thereof and battery
By coating large-particle and small-particle ternary materials through electrospinning, the preparation process is simplified, the electronic conductivity and compaction density are improved, the complex and time-consuming problems in the existing technology are solved, and the battery performance is improved.
Patent Information
- Application Number
- CN202510817424.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-18
- Publication Date
- 2025-09-12
- Estimated Expiration
- 2045-06-18
AI Technical Summary
The existing method of mixing large-particle and small-particle ternary materials is complex, time-consuming, low-yield and high-cost, resulting in poor battery performance.
The oxide and carbon capping agent are respectively coated on the outside of the premix by electrospinning to prepare coated ternary materials with different particle sizes, simplifying the preparation process and improving electronic conductivity and compaction density.
The coated ternary material prepared by electrospinning improves electronic conductivity, reduces internal resistance, enhances rate performance and compaction density, improves mechanical stress damage problems, and improves battery performance.
Smart Images

Figure CN120637473A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy batteries, and in particular to a coated ternary material mixed with different particle sizes, a preparation method thereof, and a battery. Background Art
[0002] Ternary material is a common material used to prepare the positive electrode of lithium batteries. The particle size of the ternary material will have a great impact on the performance of the battery. Among them, lithium ions need to migrate between the positive and negative electrodes during the charge and discharge process, and the size of the particles will affect the diffusion path of the lithium ions. If the particles are too large, the path of lithium ions from the inside to the surface becomes longer, which may lead to a decrease in high-rate performance. That is, when charging or discharging with large currents, the battery may perform poorly, such as rapid capacity decay or severe heat generation. Conversely, if the particles are too small, although the structure is more stable, the diffusion path is short, and the volume change is small, which can improve the rate performance, the large surface area will lead to more side reactions, which in turn shortens the life of the lithium battery.
[0003] By mixing large-particle ternary materials with small-particle ternary materials, the effect of 1+1>2 can be achieved.
[0004] However, the method of mixing large-particle ternary materials and small-particle ternary materials provided by related technologies is complex and time-consuming; and the production capacity is limited by the looseness of the materials, resulting in low production capacity and high cost. Summary of the Invention
[0005] The purpose of the present invention is to provide a coated ternary material with mixed particle sizes, a preparation method thereof, and a battery; the preparation method of the present invention is simple, has fewer steps, and can shorten the preparation time; the coated ternary material with mixed particle sizes prepared by the preparation method of the present invention can improve the electronic conductivity of the coated ternary material with mixed particle sizes, reduce internal resistance, and also improve the compaction density and rate performance; the battery prepared from the coated ternary material with mixed particle sizes of the present invention has good electrical performance.
[0006] The present invention is achieved in that: In a first aspect, the present invention provides a method for preparing a coated ternary material with mixed particles of different particle sizes, comprising mixing a nickel-cobalt-manganese precursor and a lithium salt, and then mixing the mixture with a gel solution to obtain a premix; mixing the metal oxide with the gel solution to obtain an oxide coating agent; mixing a carbon source with a gel solution to obtain a carbon coating agent; The oxide coating agent is coated on the outside of the premix by using an electrostatic spinning method to prepare an oxide-coated ternary material; The carbon coating agent is coated on the outside of the premix by using an electrospinning method to prepare a carbon-coated ternary material; Sintered oxide-coated ternary materials, carbon-coated ternary materials; The oxide-coated ternary material after sintering and the carbon-coated ternary material after sintering are mixed and blended; wherein the particle size of the oxide-coated ternary material is larger than that of the carbon-coated ternary material.
[0007] In an optional embodiment, the method of preparing the oxide-coated ternary material by coating the oxide coating agent on the outside of the premix by electrospinning specifically includes: The premix is filled into the built-in syringe of the electrospinning device, and the oxide coating agent is filled into the external syringe of the electrospinning device, and the external syringe is coaxially sleeved on the outside of the built-in syringe; then the oxide coating agent is coated on the outside of the premix by electrospinning; and / or, The method of preparing a carbon-coated ternary material by coating a carbon coating agent on the outside of a premix by an electrospinning method specifically includes: The premix is filled into the built-in syringe of the electrospinning device, and the carbon coating agent is filled into the external syringe of the electrospinning device. The external syringe is coaxially sleeved on the outside of the built-in syringe; then electrospinning is performed to coat the carbon coating agent on the outside of the premix.
[0008] In an optional embodiment, the inner diameter of the external syringe is 1.0-1.8 mm, and the inner diameter of the internal syringe is 0.3-0.6 mm.
[0009] In an optional embodiment, the voltage at which the oxide capping agent is coated on the outside of the premix by electrospinning is lower than the voltage at which the carbon capping agent is coated on the outside of the premix by electrospinning; and / or The spinning rate of coating the oxide coating agent on the outside of the premix by using the electrostatic spinning method is lower than the spinning rate of coating the carbon coating agent on the outside of the premix by using the electrostatic spinning method.
[0010] In an optional embodiment, in the step of coating the oxide coating agent on the outside of the premix by electrospinning, the electrospinning voltage is controlled to be 19.20±0.20 kV, the plate spacing is 10-15 cm, and the spinning rate is 0.2±0.1 mL / h; and / or, In the step of coating the carbon coating agent on the outside of the premix by using an electrospinning method, the electrospinning voltage is controlled to be 20.0±0.20 kV, the plate spacing is 15-20 cm, and the spinning rate is 0.6±0.2 mL / h.
[0011] In an optional embodiment, the step of sintering the oxide-coated ternary material and the carbon-coated ternary material comprises: sintering the oxide-coated ternary material and the carbon-coated ternary material respectively; wherein, In the step of sintering at least one of the oxide-coated ternary material and the carbon-coated ternary material, the temperature is raised to 400-500°C at a heating rate of 3-5°C / min for the first sintering, and then the temperature is raised to 900-1000°C at a heating rate of 3-5°C / min for the second sintering, and then cooled.
[0012] In an optional embodiment, when the sintered oxide-coated ternary material and the sintered carbon-coated ternary material are mixed, the mass ratio of the oxide-coated ternary material to the carbon-coated ternary material is 1:0.1 to 1:0.3.
[0013] In an optional embodiment, the preparation method of the gel solution comprises mixing polyacrylonitrile (PAN) and N,N-dimethylformamide (DMF), and stirring at a temperature of 40±5°C; wherein the mass ratio of polyacrylonitrile (PAN) to N,N-dimethylformamide (DMF) is 6-10%; and / or, The preparation method of the nickel-cobalt-manganese precursor comprises: dispersing nickel salt, cobalt salt and manganese salt in water to prepare a salt solution, then dropwise adding the salt solution to a citric acid-alcohol solution until a sol-gel system is formed, drying the sol-gel colloid at 200-220°C and then grinding it into powder; the total metal ion concentration in the salt solution is 0.2-0.5M, the molar ratio of the salt solution to the citric acid-alcohol solution is 1:1-1:1.5, and the mass ratio of citric acid in the citric acid-alcohol solution to the alcohol solution is 1:8-1:10; and / or, At least one of the mass ratio of the metal oxide to the nickel-cobalt-manganese precursor and the mass ratio of the carbon source to the nickel-cobalt-manganese precursor is 0.2% to 0.5%; and / or, The metal oxide includes at least one of zirconium oxide, aluminum oxide, titanium oxide, and cobalt oxide; and / or, The particle size D50 of the oxide-coated ternary material is 8-12 μm; the particle size D50 of the carbon-coated ternary material is 2-8 μm.
[0014] In a second aspect, the present invention provides a coated ternary material with mixed particles of different sizes, which is prepared by the preparation method of the coated ternary material with mixed particles of different sizes according to any one of the aforementioned embodiments; wherein, The gaps in the oxide-coated ternary material are filled with the carbon-coated ternary material; The chemical formula of the coated ternary material mixed with different particle sizes is LiNi x Co y Mn 1-x-y O2.
[0015] In a third aspect, the present invention provides a battery, wherein the raw materials for preparing the positive electrode of the battery include the coated ternary materials of the aforementioned embodiment with different particle sizes mixed.
[0016] The method for preparing a coated ternary material with mixed particles of different particle sizes of the present invention has the following beneficial effects: The preparation method provided in an embodiment of the present invention produces a large-particle oxide-coated ternary material and a small-particle carbon-coated ternary material by electrospinning, and then sintering and blending the large-particle ternary material and the small-particle ternary material to produce a coated ternary material with mixed particles of different particle sizes. Because the preparation method of the present invention utilizes electrospinning to modify the ternary material, the mechanical running-in between the coating agent and the ternary material is reduced, the operation is simple and easy, and the preparation time can be shortened, thereby improving production efficiency.
[0017] Moreover, by coating the nickel-cobalt-manganese precursor with a carbon coating agent to prepare a small-particle ternary material, and mixing the small-particle ternary material with a large-particle oxide-coated ternary material, the electronic conductivity of the coated ternary material with different particle sizes can be effectively improved, thereby reducing the internal resistance.
[0018] At the same time, the coated ternary material with different particle sizes mixed obtained by the preparation method of the present invention can improve the compaction density and rate performance, so that the production capacity is not limited by the looseness of the material; and when mixing ternary materials with different particle sizes, the friction and extrusion between the particles are reduced, which can improve the problem that the coated ternary material with different particle sizes is easily damaged by mechanical stress.
[0019] The coated ternary material with different particle sizes mixed in the present invention includes the following beneficial effects: the coated ternary material with different particle sizes mixed provided in the embodiment of the present invention is prepared by the aforementioned preparation method, and the coated ternary material with different particle sizes mixed has good electronic conductivity, small internal resistance, and also has higher compaction density and rate performance; and when mixing ternary materials with different particle sizes, the intensity of friction and extrusion between the particles is reduced, which can improve the problem that the coated ternary material with different particle sizes mixed is easily damaged by mechanical stress.
[0020] The battery of the present invention has the following beneficial effects: the raw materials for preparing the positive electrode of the battery provided in the embodiment of the present invention include the aforementioned coated ternary material mixed with different particle sizes; because the coated ternary material mixed with different particle sizes has good electronic conductivity, small internal resistance, and also has higher compaction density and rate performance, the battery prepared therefrom has good electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.
[0022] Figure 1 This is a schematic diagram of the structure of the built-in syringe and the external syringe of the electrospinning device of the present invention; Figure 2 Schematic diagram of the structure of another coated ternary material in the present invention; Figure 3 Schematic diagram of the structure of a coated ternary material in the present invention; Figure 4 This is a normal distribution diagram of the particle size of the coated ternary material mixed with different particle sizes in Example 1 of the present invention; Figure 5 This is a charge and discharge curve diagram of a test example of the coated ternary material mixed with different particle sizes in Example 1 of the present invention. DETAILED DESCRIPTION
[0023] To make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer are used. Where the manufacturer of the reagents or instruments is not specified, all are conventional products that can be purchased commercially.
[0024] Lithium ternary materials with small particle size and large specific surface area + The transmission path is shortened, supporting charging and discharging at high rates in a short time. However, due to the small size of the particles and the large specific surface area, the slurry is very easy to agglomerate during slurrying, which will lead to a decrease in the solid phase diffusion coefficient and electronic conductivity and an increase in the internal resistance of the lithium-ion battery. In order to improve the problems of the above-mentioned small-particle ternary materials and give full play to the performance of large-particle ternary materials, doping small-particle ternary materials into large-particle materials can improve the problem of easy agglomeration of small-particle materials and to a certain extent slow down the degree of deterioration of the structural stability of large-particle materials at high rates and high voltages. It can also improve the compaction density to a certain extent and affect the battery energy density.
[0025] The method provided by the related technology for mixing ternary materials of different particle sizes is solid-phase mixing, which includes: preparing a large-particle-size precursor and a small-particle-size precursor separately, and then mixing the large-particle-size precursor with a lithium source and an additive, sintering once, post-processing, coating (doping), and sintering twice; and mixing the small-particle-size precursor with a lithium source and an additive, sintering once, post-processing, coating (doping), and sintering twice.
[0026] It can be seen that the solid-phase mixing method provided by the relevant technology requires first preparing large-particle precursors and small-particle precursors separately, and then mixing, sintering, and coating the precursors with different particle sizes with lithium sources, additives, etc. Therefore, the solid-phase mixing method provided by the relevant technology is complex and time-consuming.
[0027] Moreover, the inventors have also found that the compaction density of the ternary materials with different particle sizes prepared by the solid phase mixing method provided by the related art is limited (less than 3g / cm 3 ), production capacity is still limited by the bulk of the material, with low production capacity and high preparation cost; moreover, the ternary materials with different particle sizes mixed by solid-phase mixing method have limited improvement in compaction density. When the particles are mixed, friction and extrusion are intense, and they are easily damaged by mechanical stress.
[0028] In order to simplify the preparation process and further improve the compaction density, etc., the present invention provides a new preparation method of a coated ternary material with mixed particles of different particle sizes.
[0029] The preparation method comprises: uniformly mixing nickel-cobalt-manganese precursors and lithium salts and then mixing with a gel solution to obtain a premix; mixing the metal oxide with the gel solution to obtain an oxide coating agent; mixing a carbon source with a gel solution to obtain a carbon coating agent; The oxide coating agent is coated on the outside of the premix by using an electrostatic spinning method to prepare an oxide-coated ternary material; The carbon coating agent is coated on the outside of the premix by using an electrospinning method to prepare a carbon-coated ternary material; Sintered oxide-coated ternary materials, carbon-coated ternary materials; The oxide-coated ternary material after sintering and the carbon-coated ternary material after sintering are mixed and blended; wherein the particle size of the oxide-coated ternary material is larger than that of the carbon-coated ternary material.
[0030] The preparation method prepares a large-particle oxide-coated ternary material and a small-particle carbon-coated ternary material by an electrostatic spinning method, and then sintering and mixing the large-particle ternary material and the small-particle ternary material to obtain a coated ternary material with different particle sizes. Since the preparation method of the present invention does not require additional preparation of large-particle and small-particle precursors respectively, the large-particle and small-particle precursors are sintered and coated respectively, and the electrostatic spinning method is adopted to reduce the mechanical running-in between the coating agent and the ternary material, the preparation method of the present invention is simpler, the process is relatively reduced, and the preparation time can be shortened, that is, the preparation method of the present invention can use the same nickel-cobalt-manganese precursor to directly coat oxide or carbon by electrostatic spinning to form oxide-coated ternary materials and carbon-coated ternary materials with different particle sizes, reducing the steps of preparing precursors with different particle sizes, fully reducing the preparation process, and helping to shorten the preparation time.
[0031] Moreover, by coating the nickel-cobalt-manganese precursor with a carbon coating agent to prepare a small-particle ternary material, and mixing the small-particle ternary material with a large-particle oxide-coated ternary material, the electronic conductivity of the coated ternary material with different particle sizes can be effectively improved, thereby reducing the internal resistance.
[0032] Furthermore, the coated ternary materials produced by the present invention, which are mixed with different particle sizes, can improve compaction density and rate performance, thereby freeing production capacity from being limited by the bulk of the materials. Furthermore, when mixing ternary materials of different particle sizes, the intensity of friction and compression between the particles is reduced, which can alleviate the problem of mechanical stress failure.
[0033] The positive electrode of the battery is prepared by using the coated ternary material with different particle sizes mixed and prepared by the preparation method of the present invention, so that the corresponding battery has good electrical performance.
[0034] Optionally, the preparation method of the gel solution includes: mixing polyacrylonitrile (PAN) and N,N-dimethylformamide (DMF), and stirring at a temperature of 40±5°C (for example, 35°C, 38°C, 40°C, 43°C, 45°C, etc., not specifically limited here); wherein the mass ratio of polyacrylonitrile (PAN) and N,N-dimethylformamide (DMF) is 6~10% (for example, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, etc., not specifically limited here).
[0035] Optionally, when preparing the gel solution, the solution may be stirred until transparent. The specific stirring time is not limited, for example, stirring for 12 hours, 13 hours, 10 hours, etc.
[0036] Optionally, the preparation method of the nickel-cobalt-manganese precursor includes: dispersing nickel salt, cobalt salt and manganese salt in water to prepare a salt solution, then adding the salt solution dropwise to a citric acid-alcohol solution until a sol-gel system is formed, drying the colloid of the sol-gel system at 200-220°C (for example, 200°C, 210°C, 220°C, etc.) and then grinding it into powder; wherein the total metal ion concentration in the salt solution is 0.2-0.5M (for example, 0.2M, 0.3M, 0.4M, 0.5M, etc., not specifically limited here), the mass ratio of the salt solution to the citric acid-alcohol solution is 1:1-1:1.5 (for example, 1:1, 1:1.2, 1:1.5, etc., not specifically limited here), and the mass ratio of citric acid to the alcohol solution in the citric acid-alcohol solution is 1:8-1:10 (for example, 1:8, 1:9, 1:10, etc.).
[0037] Optionally, the molar ratio of the nickel salt, the cobalt salt, and the manganese salt must precisely conform to the stoichiometric ratio of the target ternary material (eg, Ni:Co:Mn = x:y:z, X+Y+Z=1), which is not specifically limited here.
[0038] Optionally, at least one of the nickel salt, cobalt salt and manganese salt can be sulfate, nitrate, or acetate, that is, the nickel salt can be at least one of nickel sulfate, nickel nitrate and nickel acetate, the cobalt salt can be at least one of cobalt sulfate, cobalt nitrate and cobalt acetate, and the manganese salt can be at least one of manganese sulfate, manganese nitrate and manganese acetate.
[0039] Alternatively, the citric acid alcohol solution may be a citric acid-ethylene glycol aqueous solution, that is, the alcohol solution in the citric acid alcohol solution is ethylene glycol.
[0040] Optionally, the ethylene glycol may be analytically pure, that is, the mass concentration is greater than or equal to 99%.
[0041] Optionally, the molar ratio of the nickel-cobalt-manganese precursor to the lithium salt is 1:1 to 1:1.2, for example, 1:1, 1:1.02, 1:1.03, 1:1.04, 1:1.15, 1:1.2, etc., which is not specifically limited here.
[0042] Optionally, the lithium salt includes at least one of lithium sulfate, lithium nitrate, lithium acetate and lithium carbonate.
[0043] Optionally, at least one of the mass ratio of the metal oxide to the nickel-cobalt-manganese precursor and the mass ratio of the carbon source to the nickel-cobalt-manganese precursor is 0.2% to 0.5%, for example, 0.2%, 0.3%, 0.4%, 0.5%, etc., which is not specifically limited here.
[0044] Optionally, when preparing an oxide coating agent and a carbon coating agent, the gel solution taken accounts for 85% to 95% of the total mass of the coating agent (for example, 85%, 90%, 92%, 95%, etc.); when preparing a premix, the gel solution taken accounts for 40% to 65% of the total mass of the premix (for example, 40%, 50%, 55%, 60%, 65%, etc.).
[0045] Optionally, the mass ratio of the nickel-cobalt-manganese precursor to the gel solution is 1:(1-2), for example, 1:1, 1:2, etc., which is not specifically limited here.
[0046] Optionally, the metal oxide includes at least one of zirconium oxide, aluminum oxide, titanium oxide, and cobalt oxide.
[0047] Optionally, the carbon source includes but is not limited to conductive carbon black; wherein the powder resistivity of the conductive carbon black is less than 0.25Ω·cm.
[0048] Alternatively, an oxide coating agent is coated on the outside of a premix by electrospinning to prepare an oxide-coated ternary material, specifically comprising: filling the premix into a built-in syringe of an electrospinning device, filling the oxide coating agent into an external syringe of the electrospinning device, and coaxially sleeved the external syringe on the outside of the built-in syringe (see Figure 1); then electrospinning is used to coat the oxide capping agent on the outside of the premix.
[0049] Alternatively, a method for preparing a carbon-coated ternary material by coating a carbon coating agent on the outside of a premix by an electrospinning method comprises: filling the premix into a built-in syringe of an electrospinning device, filling the carbon coating agent into an external syringe of the electrospinning device, and coaxially sleeve-mounting the external syringe on the outside of the built-in syringe (see Figure 1 ); then electrospinning is used to coat the carbon capping agent on the outside of the premix.
[0050] Optionally, the inner diameter of the external syringe is 1.0-1.8 mm, for example: 1.0 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, etc., which is not specifically limited here; the inner diameter of the internal syringe is 0.3-0.6 mm, for example: 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, etc., which is not specifically limited here.
[0051] By controlling the working voltage of electrospinning and the spinning speed of the syringe, coated ternary materials with different particle sizes can be produced.
[0052] In order to make the particle size of the oxide-coated ternary material larger than that of the carbon-coated ternary material, the voltage for coating the oxide capping agent on the outside of the premixture by electrospinning is controlled to be lower than the voltage for coating the carbon capping agent on the outside of the premixture by electrospinning.
[0053] Similarly, in order to make the particle size of the oxide-coated ternary material larger than the particle size of the carbon-coated ternary material, the spinning rate of the oxide capping agent coated on the outside of the premixture by the electrospinning method is controlled to be lower than the spinning rate of the carbon capping agent coated on the outside of the premixture by the electrospinning method.
[0054] Optionally, in the step of coating the oxide coating agent on the outside of the premix by electrospinning, the process is carried out at room temperature (for example, about 25° C.) and an air humidity of less than 50% (for example, 20%, 22%, 25%, 28%, 30%, etc.), and the electrospinning voltage is controlled to be 19.20±0.20 kV (for example, 19.00 kV, 19.10 kV, 19.20 kV, 19.30 kV, 19.40 kV, etc.), the plate spacing is 10~15 cm (for example, 10 cm, 11 cm, 12 cm, 13 cm, 14 cm, 15 cm, etc.), and the spinning rate is 0.2±0.1 mL / h (for example, 0.1 mL / h, 0.2 mL / h, 0.3 mL / h, etc.).
[0055] In the step of coating the carbon coating agent on the outside of the premix by using an electrospinning method, the process is carried out at room temperature (for example, about 25° C.) and an air humidity of less than 50% (for example, 20%, 22%, 25%, 28%, 30%, etc.), and the electrospinning voltage is controlled to be 20.0±0.20 kV (for example, 19.80 kV, 19.90 kV, 20.00 kV, 20.10 kV, 20.20 kV, etc.), the plate spacing is 15-20 cm (for example, 15 cm, 16 cm, 17 cm, 18 cm, 19 cm, 20 cm, etc.), and the spinning rate is 0.6±0.2 mL / h (for example, 0.4 mL / h, 0.5 mL / h, 0.6 mL / h, 0.7 mL / h, 0.8 mL / h, etc.).
[0056] It should be noted that the above spinning rates refer to the spinning rates of both the internal syringe and the corresponding external syringe. The spinning produced by the electrospinning equipment can be collected by aluminum foil.
[0057] It should also be noted that by adjusting the working voltage and spinning rate of electrospinning, strip-shaped (filament-shaped) coated ternary materials (such as Figure 2 As shown in the figure, NCM refers to lithium nickel cobalt manganese oxide), spherical shapes can be obtained after grinding (such as Figure 3 As shown, NCM in the figure refers to lithium nickel cobalt manganese oxide).
[0058] Optionally, the oxide-coated ternary material and the carbon-coated ternary material are sintered separately; in the step of sintering at least one of the oxide-coated ternary material and the carbon-coated ternary material, the temperature is increased to 400-500°C (for example, 400°C, 430°C, 450°C, 480°C, 500°C, etc.) at a heating rate of 3-5°C / min (for example, 3°C / min, 4°C / min, 5°C / min, etc.) for the first sintering, and then the temperature is increased to 900-1000°C (for example, 900°C, 920°C, 950°C, 970°C, 1000°C, etc.) at a heating rate of 3-5°C / min (for example, 3°C / min, 4°C / min, 5°C / min, etc.) for the second sintering, and then cooled.
[0059] Optionally, when mixing the sintered oxide-coated ternary material and the sintered carbon-coated ternary material, the mass ratio of the oxide-coated ternary material to the carbon-coated ternary material is 1:0.1~1:0.3 (for example: 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, etc.).
[0060] Optionally, the particle size D50 of the oxide-coated ternary material is 8-12 μm (for example: 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, etc.); the particle size D50 of the carbon-coated ternary material is 2-8 μm (for example: 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, etc.).
[0061] The gaps in the oxide-coated ternary material of the coated ternary material with different particle sizes prepared by the preparation method of the present invention are filled with carbon-coated ternary material, and the chemical formula of the coated ternary material with different particle sizes is LiNi x Co y Mn 1-x-y O2.
[0062] The present invention also provides a battery, wherein the raw materials for preparing the positive electrode of the battery include the coated ternary material with mixed particles of different sizes prepared by the preparation method of the present invention.
[0063] It should be noted that the specific preparation method and structure of the battery are similar to those in the related art and will not be described in detail here.
[0064] The present invention is described in further detail below with reference to the examples.
[0065] Example 1 Preparation of coated ternary materials with different particle sizes 1) Dissolve 70 g of polyacrylonitrile (PAN) in 1250 mL of N,N-dimethylformamide (DMF) (approximately 6 wt%) and stir at 40°C for 12 h until transparent to obtain a gel solution.
[0066] 2) Disperse 0.6 mol nickel nitrate, 0.2 mol cobalt nitrate, and 0.2 mol manganese nitrate in 600 mL of deionized water.
[0067] 3) The salt solution obtained in step 2) is then added dropwise to a citric acid-ethylene glycol solution (the mass ratio of citric acid to ethylene glycol is 1:10) until a sol system is formed, which is then dried at 200° C. and ground into powder.
[0068] 4) The precursor and lithium carbonate obtained in step 3) were mixed uniformly and then added to the gel solution prepared in step 1) at a molar ratio of precursor to lithium carbonate of 1:1.2 and a mass ratio of precursor to gel of 1:2. The mixture was stirred for 30 minutes and then loaded into the built-in syringes (inner diameter 0.3 mm) of two electrospinning devices.
[0069] 5) Mix nano-zirconia and aluminum oxide into the gel solution from step 1), where the mass ratio of nano-zirconia to precursor is 0.3%, the mass ratio of aluminum oxide to precursor is 0.2%, and the total mass of the oxides accounts for 5% of the gel solution; stir the mixture for 30 minutes, and then load it into the external syringe (inner diameter 1.0 mm) of one of the electrospinning devices.
[0070] 6) Mix the conductive carbon black with the gel solution prepared in step 1) at a mass ratio of 1:10 (wherein the mass ratio of the conductive carbon black to the precursor is 0.5%), stir for 30 minutes, and then load the solution into an external syringe (inner diameter 1.0 mm) of another electrospinning device.
[0071] 7) Start the high-voltage electrospinning machine (at room temperature and 20% humidity) with the following process parameters: operating voltage 19.20 kV, plate spacing 10 cm, spinning rate 0.2 mL / h, and obtain a ternary material with large particles and an oxide coating on the surface.
[0072] 8) Start the high-voltage electrospinning machine (at room temperature and 20% humidity) with the following process parameters: operating voltage 20.0 kV, plate spacing 15 cm, spinning rate 0.6 mL / h, and obtain a ternary material with small particle size and a surface coating of a carbon layer.
[0073] 9) The obtained fibers were sintered separately. The first sintering was carried out by heating the fiber to 450°C at a heating rate of 3°C / min and sintering for 4 hours. The second sintering was carried out by heating the fiber to 900°C at a heating rate of 3°C / min and sintering for 12 hours. After calcination, the fiber was cooled to room temperature.
[0074] 10) The oxide-coated ternary material and the carbon-coated ternary material were mixed at a mass ratio of 1:0.15; the normal distribution diagram of the particle size of the obtained coated ternary materials with different particle sizes is shown in Figure 4 .
[0075] according to Figure 4 It can be seen that the high particle size consistency (concentrated particle size) of the coated ternary material produced by mixing different particle sizes facilitates uniform coating during battery preparation and improves battery performance stability. Furthermore, a more concentrated particle size distribution indicates a higher tap density.
[0076] Example 2 Preparation of coated ternary materials with different particle sizes 1) Dissolve 100 g of polyacrylonitrile (PAN) in 1500 mL of N,N-dimethylformamide (DMF) (approximately 7 wt %) and stir at 40°C until transparent to obtain a gel solution.
[0077] 2) Disperse 0.5 mol nickel acetate, 0.2 mol cobalt acetate, and 0.3 mol manganese acetate in 700 mL of deionized water.
[0078] 3) The salt solution obtained in step 2) is then added dropwise to a citric acid-ethylene glycol aqueous solution (the mass ratio of citric acid to ethylene glycol is 1:10) until a sol system is formed, which is then dried at 220° C. and ground into powder.
[0079] 4) The precursor and lithium acetate obtained in step 3) were mixed uniformly and then added to the gel solution prepared in step 1) at a mass ratio of 1:1.1 for the precursor and 1:1.5 for the gel solution. The mixture was stirred for 35 minutes and then loaded into the built-in syringes (inner diameter 0.6 mm) of two electrospinning devices.
[0080] 5) Titanium oxide and aluminum oxide were mixed into the gel solution prepared in step 1), wherein the mass ratio of titanium oxide to precursor was 0.2% and the mass ratio of aluminum oxide to precursor was 0.3%, and the total mass of the oxides accounted for 5% of the gel solution; the mixture was stirred for 35 minutes, and then loaded into the external syringe (inner diameter 1.8 mm) of one of the electrospinning devices.
[0081] 6) Mixing the conductive carbon black with the gel solution prepared in step 1) at a mass ratio of 1:10, wherein the mass ratio of the conductive carbon black to the precursor is 0.5%, stirring for 30 minutes, and then loading the liquid into an external syringe (inner diameter 1.8 mm) of another electrospinning device.
[0082] 7) Start the high-voltage electrospinning machine (at room temperature and 30% humidity) with the following process parameters: operating voltage 19.00 kV, plate spacing 15 cm, spinning rate 0.3 mL / h, and obtain a ternary material with large particles and an oxide coating on the surface.
[0083] 8) Start the high-voltage electrospinning machine (at room temperature and 30% humidity) with the following process parameters: operating voltage 19.8 kV, plate spacing 20 cm, spinning rate 0.8 mL / h, and obtain a ternary material with small particle size and a surface coated carbon layer.
[0084] 9) The obtained fibers were sintered separately. The first sintering was carried out by heating the fiber to 5000°C at a heating rate of 5°C / min and sintering for 3 hours. The second sintering was carried out by heating the fiber to 1000°C at a heating rate of 5°C / min and sintering for 11 hours. After calcination, the fiber was cooled to room temperature.
[0085] 10) The oxide-coated ternary material and the carbon-coated ternary material are mixed at a mass ratio of 1:0.2.
[0086] Example 3 Preparation of coated ternary materials with different particle sizes 1) Dissolve 80 g of polyacrylonitrile (PAN) in 1060 mL of N,N-dimethylformamide (DMF) (approximately 8 wt %) and stir at 42°C until transparent to obtain a gel solution.
[0087] 2) Disperse 0.3 mol nickel sulfate, 0.3 mol cobalt sulfate, and 0.3 mol manganese sulfate in 500 mL of deionized water.
[0088] 3) The salt solution obtained in step 2) is then added dropwise to a citric acid-ethylene glycol aqueous solution (the mass ratio of citric acid to ethylene glycol is 1:8) until a sol system is formed, which is then dried at 200° C. and ground into powder.
[0089] 4) The precursor and lithium sulfate obtained in step 3) were mixed uniformly and then added to the gel solution prepared in step 1) at a mass ratio of 1:1.2 between the precursor and lithium sulfate, and 1:1.2 between the precursor and gel; the mixture was stirred for 30 minutes and then loaded into the built-in syringes (inner diameter 0.5 mm) of two electrospinning devices.
[0090] 5) Mixing nano-zirconia and aluminum oxide into the gel solution prepared in step 1), wherein the mass ratio of nano-zirconia to precursor is 0.4% and the mass ratio of cobalt oxide to precursor is 0.1%, and the amount of gel solution accounts for 85% of the total mass of the coating agent; stir the mixture for 30 minutes, and then load it into the external syringe (inner diameter 1.5 mm) of one of the electrospinning devices.
[0091] 6) Mix the conductive carbon black with the gel solution prepared in step 1) at a mass ratio of 1:10, wherein the mass ratio of the conductive carbon black to the precursor is 0.2%. Stir for 30 minutes, and then load the liquid into an external syringe (inner diameter 1.5 mm) of another electrospinning device.
[0092] 7) Start the high-voltage electrospinning machine (at room temperature and 20% humidity) with the following process parameters: operating voltage 19.40 kV, plate spacing 12 cm, spinning rate 0.1 mL / h, and obtain a ternary material with large particles and an oxide coating on the surface.
[0093] 8) Start the high-voltage electrospinning machine (at room temperature and 20% humidity) with the following process parameters: operating voltage 20.20 kV, plate spacing 18 cm, spinning rate 0.4 mL / h, and obtain a ternary material with small particle size and a surface coated carbon layer.
[0094] 9) The obtained fibers were sintered separately. The first sintering was carried out by heating the temperature to 480°C at a heating rate of 4°C / min and sintering for 4 hours. The second sintering was carried out by heating the temperature to 950°C at a heating rate of 4°C / min and sintering for 10 hours. After calcination, the fibers were cooled to room temperature.
[0095] 10) The oxide-coated ternary material and the carbon-coated ternary material are mixed at a mass ratio of 1:0.2.
[0096] Test example The coated ternary materials with different particle sizes prepared in Example 1 were mixed and matched with lithium titanate as a negative electrode to make 2Ah soft-pack batteries for performance testing (test method refers to GB 31241-2022 and GB / T 31486-2015). The test results are shown in Table 1.
[0097] The battery production and testing process includes: positive electrode: binder: conductive agent = 95.7:2:2.3, the positive electrode is a coated ternary material mixed with different particle sizes, the positive electrode slurry solid content is 65%, the foil thickness is 14μm, and the coating surface density is 246g / cm 3 ; Negative electrode: binder: conductive agent = 94:3.0:3.0, the negative electrode is lithium titanate, the negative electrode slurry solid content is 55%, and the surface density is 214g / cm 3 The molar ratio of the electrolyte components is DMC:EMC:EC:LiPF6=31.5:33.5:17.5:17.5.
[0098] Table 1
[0099] From the test results in Table 1, we can see that 96μm is the ultimate compaction density. According to the formula: compaction density = surface density / (roller thickness - foil thickness), the actual compaction density is calculated to be 3.0g / cm 3 The folding effect diagram is shown in Table 1. The formation temperature is 90℃, and the battery test data (charge and discharge curve after 500 cycles) is as follows Figure 5 .
[0100] Comparative Example 1 The large-particle coated ternary material prepared in step 7) of Example 1 was used with lithium titanate as a negative electrode to make a 2Ah soft-pack battery for performance testing (test method refers to GB 31241-2022 and GB / T 31486-2015). The test results are shown in Table 2.
[0101] The battery production and testing process includes: positive electrode: binder: conductive agent = 95.7:2:2.3, the positive electrode is a coated ternary material mixed with different particle sizes, the positive electrode slurry solid content is 65%, the foil thickness is 14μm, and the coating surface density is 246g / cm 3; Negative electrode: binder: conductive agent = 94:3.0:3.0, the negative electrode is lithium titanate, the negative electrode slurry solid content is 55%, and the surface density is 214g / cm 3 The molar ratio of the electrolyte components is DMC:EMC:EC:LiPF6=31.5:33.5:17.5:17.5.
[0102] Table 2
[0103] From the test results in Table 2, we can see that 108μm is the ultimate compaction density. According to the formula: compaction density = surface density / (roller thickness - foil thickness), the actual compaction density is calculated to be 2.61g / cm 3 The folding effect diagram is shown in Table 2. The formation temperature is 90℃, and the battery test data (charge and discharge curve after 500 cycles) is as follows: Figure 5 .
[0104] Comparative Example 2 The small-particle coated ternary material prepared in step 8) of Example 1 was used with lithium titanate as a negative electrode to make a 2Ah soft-pack battery for performance testing (test method refers to GB 31241-2022 and GB / T 31486-2015). The test results are shown in Table 3.
[0105] The battery production and testing process includes: positive electrode: binder: conductive agent = 95.7:2:2.3, the positive electrode is a coated ternary material mixed with different particle sizes, the positive electrode slurry solid content is 65%, the foil thickness is 14μm, and the coating surface density is 246g / cm 3 ; Negative electrode: binder: conductive agent = 94:3.0:3.0, the negative electrode is lithium titanate, the negative electrode slurry solid content is 55%, and the surface density is 214g / cm 3 The molar ratio of the electrolyte components is DMC:EMC:EC:LiPF6=31.5:33.5:17.5:17.5.
[0106] Table 3
[0107] From the test results in Table 3, we can see that 156μm is the ultimate compaction density. According to the formula: compaction density = surface density / (roller thickness - foil thickness), the actual compaction density is calculated to be 1.73g / cm 3 The folding effect diagram is shown in Table 3. The formation temperature is 90℃, and the battery test data (charge and discharge curve after 500 cycles) is as follows: Figure 5 .
[0108] According to the above records, as well as Table 1, Table 2, Table 3, and Figure 5It can be seen that the performance of the coated ternary material with different particle sizes mixed in Example 1 is better than that of the ternary material with a single particle size. The positive electrode of the battery prepared from the material of Example 1 has a higher compaction density and better electrical performance.
[0109] In summary, the preparation method of the coated ternary material with different particle sizes mixed according to the present invention is simple, has fewer steps, and can shorten the preparation time; and the coated ternary material with different particle sizes mixed prepared by the preparation method of the present invention can improve the electronic conductivity of the coated ternary material with different particle sizes mixed, reduce the internal resistance, and also improve the compaction density and rate performance; the battery prepared from the coated ternary material with different particle sizes mixed according to the present invention has good electrical properties.
[0110] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. A method for preparing a coated ternary material with mixed particles of different sizes, characterized by: mixing a nickel-cobalt-manganese precursor and a lithium salt, and then mixing the mixture with a gel solution to obtain a premix; mixing a metal oxide with the gel solution to obtain an oxide coating agent; mixing a carbon source with the gel solution to obtain a carbon coating agent; The oxide coating agent is coated on the outside of the premix by an electrostatic spinning method to prepare an oxide-coated ternary material; The carbon coating agent is coated on the outside of the premix by an electrostatic spinning method to prepare a carbon-coated ternary material; sintering the oxide-coated ternary material and the carbon-coated ternary material; The oxide-coated ternary material after sintering and the carbon-coated ternary material after sintering are mixed; wherein the particle size of the oxide-coated ternary material is larger than the particle size of the carbon-coated ternary material.
2. The method for preparing the coated ternary material with mixed particles of different particle sizes according to claim 1, characterized in that: The method of using an electrostatic spinning method to coat the oxide coating agent on the outside of the premix to prepare the oxide-coated ternary material specifically includes: The premix is filled into a built-in syringe of an electrospinning device, and the oxide coating agent is filled into an external syringe of the electrospinning device, wherein the external syringe is coaxially sleeved on the outside of the built-in syringe; then, the oxide coating agent is coated on the outside of the premix by electrospinning; and / or, The method of using electrostatic spinning to coat the carbon coating agent on the outside of the premix to prepare the carbon-coated ternary material specifically includes: The premix is filled in the built-in syringe of the electrospinning device, and the carbon coating agent is filled in the external syringe of the electrospinning device, and the external syringe is coaxially sleeved on the outside of the built-in syringe; then electrospinning is performed to coat the carbon coating agent on the outside of the premix.
3. The method for preparing the coated ternary material with mixed particles of different particle sizes according to claim 2, characterized in that: The inner diameter of the external syringe is 1.0-1.8 mm, and the inner diameter of the internal syringe is 0.3-0.6 mm.
4. The method for preparing a coated ternary material having mixed particles of different particle sizes according to any one of claims 1 to 3, characterized in that: The voltage at which the oxide coating agent is coated on the outside of the premix by electrostatic spinning is lower than the voltage at which the carbon coating agent is coated on the outside of the premix by electrostatic spinning; and / or, The spinning rate of coating the oxide coating agent on the outside of the premix by using the electrostatic spinning method is lower than the spinning rate of coating the carbon coating agent on the outside of the premix by using the electrostatic spinning method.
5. The method for preparing coated ternary materials with mixed particles of different particle sizes according to claim 4, characterized in that: In the step of coating the oxide coating agent on the outside of the premix by electrospinning, the electrospinning voltage is controlled to be 19.20±0.20 kV, the plate spacing is 10-15 cm, and the spinning rate is 0.2±0.1 mL / h; and / or, In the step of coating the carbon coating agent on the outside of the premix by using an electrospinning method, the electrospinning voltage is controlled to be 20.0±0.20 kV, the plate spacing is 15-20 cm, and the spinning rate is 0.6±0.2 mL / h.
6. The method for preparing a coated ternary material with mixed particles of different sizes according to any one of claims 1 to 3, characterized in that: The step of sintering the oxide-coated ternary material and the carbon-coated ternary material comprises: sintering the oxide-coated ternary material and the carbon-coated ternary material respectively; wherein, In the step of sintering at least one of the oxide-coated ternary material and the carbon-coated ternary material, the temperature is raised to 400-500°C at a heating rate of 3-5°C / min for the first sintering, and then the temperature is raised to 900-1000°C at a heating rate of 3-5°C / min for the second sintering, and then cooled.
7. The method for preparing a coated ternary material with mixed particles of different sizes according to any one of claims 1 to 3, characterized in that: When the sintered oxide-coated ternary material and the sintered carbon-coated ternary material are mixed, the mass ratio of the oxide-coated ternary material to the carbon-coated ternary material is 1:0.1 to 1:0.
3.
8. The method for preparing a coated ternary material with mixed particles of different sizes according to any one of claims 1 to 3, characterized in that: The preparation method of the gel solution comprises mixing polyacrylonitrile and N,N-dimethylformamide, and stirring at a temperature of 40±5° C.; wherein the mass ratio of the polyacrylonitrile to the N,N-dimethylformamide is 6-10%; and / or, The preparation method of the nickel-cobalt-manganese precursor comprises: dispersing nickel salt, cobalt salt and manganese salt in water to prepare a salt solution, then dropwise adding the salt solution into a citric acid-alcohol solution until a sol-gel system is formed, drying the colloid of the sol-gel system at 200-220° C. and then grinding it into powder; wherein the total metal ion concentration in the salt solution is 0.2-0.5 M, the molar ratio of the salt solution to the citric acid-alcohol solution is 1:1-1:1.5, and the mass ratio of citric acid in the citric acid-alcohol solution to the alcohol solution is 1:8-1:10; and / or, At least one of the mass ratio of the metal oxide to the nickel-cobalt-manganese precursor and the mass ratio of the carbon source to the nickel-cobalt-manganese precursor is 0.2% to 0.5%; and / or, The metal oxide includes at least one of zirconium oxide, aluminum oxide, titanium oxide and cobalt oxide; and / or, The particle size D50 of the oxide-coated ternary material is 8-12 μm; the particle size D50 of the carbon-coated ternary material is 2-8 μm.
9. A coated ternary material with mixed particles of different sizes, characterized by: It is prepared by the preparation method of the coated ternary material with different particle sizes mixed according to any one of claims 1 to 8; wherein, The gaps in the oxide-coated ternary material are filled with the carbon-coated ternary material; The chemical formula of the coated ternary material with different particle sizes is LiNi x Co y Mn 1-x-y O2.
10. A battery, characterized in that: The raw materials for preparing the positive electrode of the battery include the coated ternary material with different particle sizes mixed as described in claim 9.
Citation Information
Patent Citations
Preparation method of carbon-coated nano nickel-lithium battery material
CN111564619A
Ternary positive electrode material doped, coated and modified by fast ion conductor and preparation method of material
CN112599756A
Preparation method and application of low-residual-alkali high-nickel ternary positive electrode material
CN117497686A
Ternary positive electrode material and lithium ion battery and battery module thereof
CN119181782A
Positive pole piece, battery and electric device
CN119856294A